Electrochemical properties of α-MoO3-coated Li[Li0.2Mn0.54Ni0.13Co0.13]O2 cathode material for Li-ion batteries. (10th September 2015) - Wang, Chunlei; Zhou, Fei; Chen, Kangmin; Kong, Jizhou; Jiang, Youxuan; Yan, Guozhen; Li, Junxiu; Yu, Chao; Tang, Wei-Ping
Highlights: MoO3 -coated Li[Li0.2 Mn0.54 Ni0.13 Co0.13 ]O2 is synthesized successfully. The initial Coulombic efficiency increases from 71.2% to 79.3% when the MoO3 content increases The discharge capacities and capacity retentions first increase, and then decrease with the MoO3 content. 3 wt.%MoO3 -coated Li[Li0.2 Mn0.54 Ni0.13 Co0.13 ]O2 possesses the best cycle stability and rate capability. Abstract: MoO3 -coated Li[Li0.2 Mn0.54 Ni0.13 Co0.13 ]O2 cathode materials were synthesized via using co-precipitation method and wet coating process, and their crystal structure and particle morphology were analyzed and observed by XRD, SEM and TEM. The electrochemical properties of these materials were investigated and analyzed by using charge-discharge tests and electrochemical impedance spectroscopy. The results showed that the surface coating on Li[Li0.2 Mn0.54 Ni0.13 Co0.13 ]O2 cathode was composed of α-MoO3 and Li2 MoO4, and the electrochemical properties were improved after coated with MoO3 thin films. The initial coulombic efficiencies increased from 71.2% to 79.3% when the MoO3 content increased to 5 wt.%. Particularly, the 3 wt.% MoO3 -coated Li[Li0.2 Mn0.54 Ni0.13 Co0.13 ]O2 showed the highest capacity retention of 90.8% after 100 cycles, and possessed the excellent rate discharge performance. The electrochemical impedance spectroscopy (EIS) and cyclic voltammetric results demonstrated that the layered MoO3 coating could restrain the increment of the charge transfer resistance and stabilize the active material structure during cyclic process.